1998
DOI: 10.1063/1.121274
|View full text |Cite
|
Sign up to set email alerts
|

Deep centers in n-GaN grown by reactive molecular beam epitaxy

Abstract: Deep centers in Si-doped n-GaN layers grown by reactive molecular beam epitaxy have been studied by deep-level transient spectroscopy as a function of growth conditions. Si-doped GaN samples grown on a Si-doped n+-GaN contact layer at 800 °C show a dominant trap C1 with activation energy ET=0.44 eV and capture cross-section σT=1.3×10−15 cm−2, while samples grown at 750 °C on an undoped semi-insulating GaN buffer show prominent traps D1 and E1, with ET=0.20 eV and σT=8.4×10−17 cm2, and ET=0.21 eV and σT=1.6×10−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
65
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(75 citation statements)
references
References 10 publications
10
65
0
Order By: Relevance
“…Therefore, in our case, we believe that the plasma treatments do not cause any meaningful increase in dislocation density, even under an etching biasvoltage of Ϫ150 V. Trap D, with E T ϭ0.23-0.27 eV and n ϭ(1 -2)ϫ10 Ϫ15 cm 2 , has been observed in thin GaN layers by many groups, using various techniques, including hydride vapor phase epitaxy ͑HPVE͒, [8][9][10] MOCVD, [11][12][13] and MBE. 14,15 Three of these studies are consistent with the proposition that trap D is at least sometimes related to threading dislocations. For example, the concentration of trap D in HVPE GaN increases with increasing dislocation density, corresponding to decreasing epilayer thickness.…”
supporting
confidence: 72%
“…Therefore, in our case, we believe that the plasma treatments do not cause any meaningful increase in dislocation density, even under an etching biasvoltage of Ϫ150 V. Trap D, with E T ϭ0.23-0.27 eV and n ϭ(1 -2)ϫ10 Ϫ15 cm 2 , has been observed in thin GaN layers by many groups, using various techniques, including hydride vapor phase epitaxy ͑HPVE͒, [8][9][10] MOCVD, [11][12][13] and MBE. 14,15 Three of these studies are consistent with the proposition that trap D is at least sometimes related to threading dislocations. For example, the concentration of trap D in HVPE GaN increases with increasing dislocation density, corresponding to decreasing epilayer thickness.…”
supporting
confidence: 72%
“…Presently, the main wide band gap materials for space applications are considered to be the III-V nitrides, SiC, and diamond. Whereas the effect of high-energy electron irradiation has been reported for ZnO, 3 GaN, 4,5 and SiC, 6 no data are yet available regarding the exposure of ZnO to heavier particles such as protons and He-ions, as was reported for GaN. 7,8 In particular, to our knowledge, data pertaining to radiation-and implantation-induced deep level defects in ZnO are not yet available.…”
mentioning
confidence: 63%
“…Evaluating this ex-pression requires knowledge of the room temperature capture cross section of the traps being investigated in this work. While such data are not available for the traps considered here, capture cross sections in HR and n-type GaN have been reported [23][24][25] in a broad range from roughly 10 Ϫ23 cm 2 to 10 Ϫ15 cm 2 . Polyakov et al 25 have reported capture cross sections for GaN near room temperature for the E2 center ͓ c (278 K)ϭ4ϫ10 Ϫ20 cm 2 ] and the E4 center ͓ c (385 K)ϭ3.3ϫ10 Ϫ23 cm 2 ].…”
Section: ͑29͒mentioning
confidence: 99%